Insights Into the Dynamics and Composition of Biofilm Formed by Environmental Isolate of Enterobacter cloacae - Misra, Tripti; Tare, Meghana; Jha, Prabhat Nath (Frontiers in Microbiology, 2022)
Bacterial biofilms are clinically admissible and illustrate an influential role in infections, especially those related to the implant of medical devices. Characterizing biofilms is important to understand the etiology of the diseases. Enterobacter cloacae are known for causing infections by forming biofilms on various abiotic surfaces such as medical devices. However, a detailed characterization in terms of morphology and the molecular composition of the formed biofilms by this bacterium is sparse. The present study provides insights into the biofilm formation of E. cloacae SBP-8, an environmental isolate, on various surfaces. We performed assays to understand the biofilm-forming capability of the SBP-8 strain and characterized the adhering potential of the bacteria on various medical device surfaces at different temperatures. We also found that medical devices exhibited strong colonization by E. cloacae SBP-8. Using field emission-scanning electron microscopy (FE-SEM) studies, we characterized the biofilms as a function of time. We used surface-enhanced Raman spectroscopy (SERS) and identified the vast heterogenic nature of the biofilm-forming molecules. Interestingly, we also found that this heterogeneity varies from the initial stages of biofilm formation until the maturation and dispersion. Our studies provide insights into biofilm composition over a period of time, which might aid in understanding the biofilm dispersion phases, to enhance the presently available treatment strategies.